The mediator role of routines on the relationship between general procrastination, academic procrastination and perceived importance of sleep and bedtime procrastination - Magalhães, Paula (2021)
Background: Sleep plays a key role in our overall function, and sleep insufficiency has been highlighted as a major health issue. ‘Bedtime procrastination’—i.e., needlessly delaying the time one goes to bed without external reasons—is one reason for sleep insufficiency. The present research aims to explore the interrelationships among Bedtime Procrastination, other domains of Procrastination, and routine-related variables. Methods: The mediating effects of Wake-up Time and Dinner Time on the relationship between Bedtime Procrastination and General Procrastination, Academic Procrastination, and Perceived Importance of Sleep were tested. Self-reported questionnaires were used, and the sample comprised of 446 university students. Results: A partial mediation model was found. General Procrastination, Academic Procrastination, and Perceived Importance of Sleep showed direct effects on Bedtime Procrastination. Moreover, Academic and General Procrastination were positively associated with Bedtime Procrastination, whereas Perceived Importance of Sleep was negatively associated with Bedtime Procrastination. Indirect effects of the Perceived Importance of Sleep and General Procrastination, as mediated by Wake-up Time and Dinner Time, on Bedtime Procrastination were also found. Conclusions: Personal routines (Wake-up Time and Dinner Time) along with individual characteristics (General and Academic Procrastination) and beliefs (perceived importance of sleep) may affect Bedtime Procrastination. Present results highlight the complexity of Bedtime Procrastination.